PENGEMBANGAN POTENSI PRODUKSI USAHA MIKRO, KECIL, DAN MENENGAH DI PONDOK PESANTREN MELALUI PENDAMPINGAN HAK KEKAYAAN INTELEKTUAL - Hidayat Putri, Zora Febriena Dwithia; Ganindha, Ranitya (Jurnal Hukum Bisnis Bonum Commune, 2022)
Islamic boarding schools as one of the educational facilities are currently starting to develop their potential in the economic field by establishing business centers. Most of the businesses owned by pesantren are micro, small and medium scale enterprises (MSMEs). MSMEs are considered to play an important role in Indonesia's economic activities because most businesses in Indonesia are small businesses that absorb a lot of labor. However, significant developments in terms of quantity have not been accompanied by developments in terms of quality. The purpose of this study is to analyze the mapping of potential business products from Islamic boarding schools in Malang, analyze the obstacles faced by MSMEs in Islamic boarding schools in product innovation about ntellectual Property Rights. for MSMEs to increase production potential. This study employs Juridical Empirical research. The focus of this research is the protection of IPR for MSMEs in Islamic boarding schools in Malang. Based on the results of the study, it can be concluded that the potential of MSME products owned by Islamic boarding schools in Malang City is currently quite diverse, ranging from supermarkets which are not only limited to internal boarding schools but also for the surrounding community. This activity also opens up opportunities for opening up job opportunities for many people as well as providing entrepreneurial education for students. Given the enormous benefits, this potential needs to be continuously supported and developed from various aspects, one of which is in terms of guaranteeing legal protection for MSME products of Islamic boarding schools through IPR assistance. Constraints faced by MSMEs in Islamic boarding schools in product innovation in relation to Intellectual Property Rights include: lack of detailed understanding of legal protection for MSME actors; stages of trademark registration that are considered difficult. Management is considered to only be able to be done directly and cannot use an online mechanism so that it will require quite a lot of costs; and product exclusivity is not the main thing, business competition is not too tight. IPR protection for MSME products is needed to prevent ideas that are owned and then stolen and used by other parties. Some forms of IPR protection that can be given to MSME products in Islamic boarding schools are through copyright management, brand rights, and having trade secrets.